2018
DOI: 10.1016/j.ejvs.2017.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Assessment of the Angiosome Concept by Intra-operative Fluorescence Angiography After Tibial Bypass Surgery

Abstract: Microcirculatory improvement was seen over the whole foot after tibial bypass. Therefore, fluorescence angiography is a promising tool to evaluate the angiosome concept in future larger studies. Clinicaltrials.gov: NCT03012750.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…This paper reveals better and quicker healing results for intentional endovascular DR, however with no significant difference in limb salvage and amputation free survival between groups [89]. In another up-to-date 40 cases prospective analysis, Rother et al [90] found a notable difference in "time to healing" for bypass that was superior in DR against IR. The authors observed yet no meaningful significance in immediate microcirculation changes between the studied groups [90].…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 64%
See 1 more Smart Citation
“…This paper reveals better and quicker healing results for intentional endovascular DR, however with no significant difference in limb salvage and amputation free survival between groups [89]. In another up-to-date 40 cases prospective analysis, Rother et al [90] found a notable difference in "time to healing" for bypass that was superior in DR against IR. The authors observed yet no meaningful significance in immediate microcirculation changes between the studied groups [90].…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 64%
“…In another up-to-date 40 cases prospective analysis, Rother et al [90] found a notable difference in "time to healing" for bypass that was superior in DR against IR. The authors observed yet no meaningful significance in immediate microcirculation changes between the studied groups [90]. These two recent prospective studies seem but to confirm previous retrospective tissue healing observations about quicker median time to "tissue recovery" following DR/WTR Recent clinical correlations.…”
Section: Current Literature Review Concerning Dr/wtr Strategiesmentioning
confidence: 98%
“…Methods of tissue engineering and regenerative medicine [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] to circumvent the use of autologous tissue and their inherent donor site morbidity seem promising but are not clinically available for these problems yet. Although a considerable number of local or free flaps has been successfully described to surgically reconstruct these defects [7,[52][53][54][55][56][57][58] each individual case needs the optimal indication for the most suitable flap procedure. Free flap transfer has become a routine method in high volume centers and allow free tissue transfer even to the distal lower extremity with a successful closure in more than 90%-95%, depending on the comorbidities and local and systemic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Neben der Wahl eines geeigneten Perforators ist die intraoperative Beurteilung der Perfusion einer Lappenplastik entscheidend um lappenbedingte Komplikationen zu vermeiden. Anhand von ICG-Fluoreszenzangiographie, Laser-Doppler Spektrometrie, dynamischer Infrarot-Thermografie und Photospektrometrie kann die Gewebeperfusion objektiv dargestellt werden [33][34][35][36]. In Anbetracht der Tatsache, dass die ICG-Fluoreszenzangiographie das hierbei mit Abstand am häufigsten verwendete Tool ist, was sich auch in unserem Konsensus Workshop bestätigte, wird im Folgenden lediglich diese Methode diskutiert.…”
Section: Diskussionunclassified